2017
DOI: 10.5455/ajvs.259758
|View full text |Cite
|
Sign up to set email alerts
|

Detection of B. Cereus and Some of Its Virulence Genes in Some Dairy Desserts and Children Diarrhea

Abstract: Key words: B. cereus, Dairy desserts, Diarrhea and virulence genesB. cereus is an opportunistic foodborne pathogen that is found in most of the cases to be responsible for food-borne outbreaks. This study aimed to detect and quantify B. cereus in dairy desserts that locally manufactured and sold in different localities in Qena city, also to take an image about the role that is may be played by these products in causing foodborne illness by detection of B. cereus in diarrheal samples collected from the same reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…In this study Bacillus cereus has been isolated from 58% of pudding (mahallbia) samples with mean count of 8.38× 10 5 CFU/g and approximately similar results were reported by (13,17). Lower incidences have been reported 44% and 48% by (4,16) respectively but with lower mean value of 3.83×10 5 CFU/g (16).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In this study Bacillus cereus has been isolated from 58% of pudding (mahallbia) samples with mean count of 8.38× 10 5 CFU/g and approximately similar results were reported by (13,17). Lower incidences have been reported 44% and 48% by (4,16) respectively but with lower mean value of 3.83×10 5 CFU/g (16).…”
Section: Discussionsupporting
confidence: 87%
“…CFU/g. Higher incidence has been recorded 76.6% with ahigher mean value of 1.4 ×10 7 ± 6.6 × 10 6 CFU/g by (13).lower results were recorded 64% with ahigher mean value of 2.4×107± 1.5× 107 CFU/g by (4). Lower incidences have been reported 60% ,55% , 48% ,35% and 15% from rice pudding samples by (32,27,16,30,17) respectively.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Reis et al (15) reported that 36.5% of isolated B. cereus from pasteurized, sterilized and dry milk in Brazil had the hbl complex genes. In another study, El-zamkan and Mubarak in Egypt (16), has been reported that the frequency of the hbl complex genes in B. cereus isolated from ice cream and rice-milk was 33.3% and 43.5%, respectively (16). Differences in distribution of the hbl complex genes in different B. cereus isolates in the mentioned studies probably are due to the geographical differences and the differences in ecological origin of isolated strains from milk, rice, meat, salads.…”
Section: Discussionmentioning
confidence: 93%